Challenges in the Transnational Business Education: Learning and Teaching Perspectives from Australia and Singapore - Pimpa, Nattavud; Heffernan, Margaret (Journal of International Students, 2020)
Management of learning and teaching in a transnational business education program can be a true challenge for institutions in both home and host countries, especially with leadership and governance. In this article, we seek to define challenges in engaging business students in a transnational education program operating in Singapore and Australia. From the interviews with students and staff, we identified feedback, communication, and transferability as important factors promoting engagement among students in the transnational program. We highlight learning strategies to support ongoing engagement among students in a transnational business education program. The findings suggest that contextualizing the local and international issues is crucial in the management of a transnational business education program if students are to develop global competencies.